Association of Pre-diagnostic Antibody Responses to Escherichia coli and Bacteroides fragilis Toxin Proteins with Colorectal Cancer in a European Cohort. (1st January 2021) - Butt, Julia; Jenab, Mazda; Werner, Jill; Fedirko, Veronika; Weiderpass, Elisabete; Dahm, Christina C.; Tjønneland, Anne; Olsen, Anja; Boutron-Ruault, Marie-Christine; Rothwell, Joseph A.; Severi, Gianluca; Kaaks, Rudolf; et al.
ABSTRACT: Experimental evidence has implicated genotoxic Escherichia coli ( E. coli ) and enterotoxigenic Bacteroides fragilis (ETBF) in the development of colorectal cancer (CRC). However, evidence from epidemiological studies is sparse. We therefore assessed the association of serological markers of E. coli and ETBF exposure with odds of developing CRC in the European Prospective Investigation into Nutrition and Cancer (EPIC) study. Serum samples of incident CRC cases and matched controls (n = 442 pairs) were analyzed for immunoglobulin (Ig) A and G antibody responses to seven E. coli proteins and two isoforms of the ETBF toxin via multiplex serology. Multivariable-adjusted conditional logistic regression analyses were used to estimate odds ratios (ORs) and 95% confidence intervals (CIs) for the association of sero-positivity to E. coli and ETBF with CRC. The IgA-positivity of any of the tested E. coli antigens was associated with higher odds of developing CRC (OR: 1.42; 95% CI: 1.05–1.91). Dual-positivity for both IgA and IgG to E. coli and ETBF was associated with >1.7-fold higher odds of developing CRC, with a significant association only for IgG (OR: 1.75; 95% CI: 1.04, 2.94). This association was more pronounced when restricted to the proximal colon cancers (OR: 2.62; 95% CI: 1.09, 6.29) compared to those of the distal colon (OR: 1.24; 95% CI: 0.51, 3.00) ( pheterogeneity = 0.095). Sero-positivity to E. coli and ETBF was associated with CRC development, suggesting that co-infection of these bacterial species may contribute to colorectal carcinogenesis. These findings warrant further exploration in larger prospective studies and within different population groups.